THE ROLE OF THE PAMONG PRAJA POLICE UNIT IN IMPLEMENTING ORDER IN THE KARAWANG PUBLIC SPACE - Pebriyani, Pebriyani; Dewi, Sartika; Abas, Muhamad (Universitas Islam Negeri Ar-Raniry, 2024)
Local governments are required to build public facilities and spaces for the benefit of the community. The success of a government is measured by its ability to construct safe and comfortable facilities. Public facilities must be maintained to ensure community comfort. The Civil Service Police Unit (Satpol PP) of Karawang Regency deploys its members in public spaces to maintain order. This qualitative research uses an empirical juridical approach to understand the roles and challenges of Satpol PP. The findings aim to improve the effectiveness of Satpol PP in maintaining public order in open spaces.